Beban Kerja Perawat dengan Reseliensi di Rumah Sakit Islam Purwokerto - Etlidawati Etlidawati; Retno Sulistiyowati; Alfi Noviyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study analyzes the relationship between nurse workload and resilience at the Islamic Hospital in Purwokerto. This research method is quantitative research using a correlation design with a cross-sectional approach. The results showed that the light workload was 56% and the heavy workload was 44%. Low resolution 73%, high resolution 27%. The test results obtained a p-value of 0.003 with an OR of 0.435. In conclusion, there is a strong relationship between nurse workload and resilience in the inpatient room of the Purwokerto Islamic Hospital Keywords: Workload, Nurses, Resilience